Development of a Novel Soft Tissue Measurement Device for Individualized Finite Element Modeling in Custom-Fit CPAP Mask Evaluation - Martelly, Erica; Lee, Summer; Martinez, Kristina; Rana, Sandeep; Shimada, Kenji (Annals of biomedical engineering, 2024)
Purpose Individual facial soft tissue properties are necessary for creating individualized finite element (FE) models to evaluate medical devices such as continuous positive airway pressure (CPAP) masks. There are no standard tools available to measure facial soft tissue elastic moduli, and techniques in literature require advanced equipment or custom parts to replicate. Methods We propose a simple and inexpensive soft tissue measurement (STM) indenter device to estimate facial soft tissue elasticity at five sites: chin, cheek near lip, below cheekbone, cheekbone, and cheek. The STM device consists of a probe with a linear actuator and force sensor, an adjustment system for probe orientation, a head support frame, and a controller. The device was validated on six ballistics gel samples and then tested on 28 subjects. Soft tissue thickness was also collected for each subject using ultrasound. Results Thickness and elastic modulus measurements were successfully collected for all subjects. The mean elastic modulus for each site is E c = 53.04 ± 20.97 kPa for the chin, E l = 16.33 ± 8.37 kPa for the cheek near lip, E bc = 27.09 ± 11.38 kPa for below cheekbone, E cb = 64.79 ± 17.12 kPa for the cheekbone, and E ch = 16.20 ± 5.09 kPa for the cheek. The thickness and elastic modulus values are in the range of previously reported values. One subject’s measured soft tissue elastic moduli and thickness were used to evaluate custom-fit CPAP mask fit in comparison to a model of that subject with arbitrary elastic moduli and thickness. The model with measured values more closely resembles in vivo leakage results. Conclusion Overall, the STM provides a first estimate of facial soft tissue elasticity and is affordable and easy to build with mostly off-the-shelf parts. These values can be used to create personalized FE models to evaluate custom-fit CPAP masks.